Educational Strategies for Mitigating Religion-Based Conflict Potential in Indonesia: A Qualitative Multiple-Case Study Across Urban and Rural Communities - Ikhwan Sawaty; Elihami, Elihami (Edumaspul: Jurnal Pendidikan, 2024)
Religion-based conflicts remain a significant challenge to maintaining social cohesion in Indonesia, a nation historically recognized for its rich religious and cultural diversity. Religious sentiments expressed in both face-to-face interactions and digital spaces frequently contribute to social tensions, particularly in communities with high levels of social vulnerability. From an educational perspective, strengthening peace education, interfaith dialogue, and multicultural learning is essential for preventing the escalation of religious tensions and fostering sustainable social harmony. This study aims to examine educationally informed strategies for mitigating religion-based conflicts in selected urban and rural areas characterized by latent conflict potential. A qualitative multiple-case study design was employed across five strategic regions: Jakarta, Surakarta, Ambon, Poso, and Tasikmalaya. Data were collected through in-depth interviews with religious leaders, community leaders, and education stakeholders, complemented by participant observation and analysis of local policy documents. The findings reveal that effective conflict mitigation is strongly influenced by three interconnected factors: the strength of interfaith social networks, the mediation capacity of local actors, and adaptive public policies responsive to local socio-cultural dynamics. In urban settings, the active role of Interfaith Harmony Forums (FKUB), educational institutions, and digital campaigns promoting religious moderation significantly contributed to preventing conflict escalation. In rural communities, educational initiatives grounded in local wisdom, community reconciliation, and culturally responsive learning proved more effective in strengthening mutual understanding and social resilience. The study recommends enhancing the capacity of educators, religious leaders, and community facilitators while integrating structural and cultural approaches into educational policies and conflict mitigation frameworks. These findings highlight the strategic role of education as a transformative instrument for promoting religious tolerance, social cohesion, and sustainable peace in multicultural societies.